2002
DOI: 10.4049/jimmunol.169.12.6842
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of IL-12 in Providing a Third Signal for Clonal Expansion of Naive CD8 T Cells

Abstract: Stimulation of an effective in vitro or in vivo response by naive CD8 T cells requires three signals: TCR engagement, costimulation/IL-2, and a third signal that can be provided by IL-12. In addition to being required for acquisition of cytolytic function, IL-12 is required for optimal IL-2-dependent proliferation and clonal expansion. In experiments examining in vitro stimulation of naive CD8 T cells, IL-12 is shown to stimulate expression of the IL-2R α-chain (CD25) to much higher levels than are reached in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
190
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(207 citation statements)
references
References 54 publications
13
190
3
1
Order By: Relevance
“…In support of these findings, Chang et al reported that IL-12 priming at the time of antigenic stimulation increased the primary expansion of CD8 + T cells by reducing cell death, rather that by increasing cell proliferation, resulting in a larger CD8 + T cell memory pool [4]. The ability of IL-12 to enhance proliferation of activated CD8 + T cells has been recently associated with enhanced expression of IL-2Rα in response to IL-12R engagement [35]. IL-12R expression is upregulated upon TCR activation [9], however low levels of expression have been reported in resting NK cells, dendritic cells and B cell lines [1,12].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In support of these findings, Chang et al reported that IL-12 priming at the time of antigenic stimulation increased the primary expansion of CD8 + T cells by reducing cell death, rather that by increasing cell proliferation, resulting in a larger CD8 + T cell memory pool [4]. The ability of IL-12 to enhance proliferation of activated CD8 + T cells has been recently associated with enhanced expression of IL-2Rα in response to IL-12R engagement [35]. IL-12R expression is upregulated upon TCR activation [9], however low levels of expression have been reported in resting NK cells, dendritic cells and B cell lines [1,12].…”
Section: Discussionsupporting
confidence: 49%
“…IL-12 can also directly affect the development of CD8 + T cell-mediated responses. It is known that optimal clonal expansion and acquisition of effector function requires a third signal that can be provided by IL-12, and that in the absence of third signal, tolerance can occur [6,7,29,30,35,36]. In support of these findings, Chang et al reported that IL-12 priming at the time of antigenic stimulation increased the primary expansion of CD8 + T cells by reducing cell death, rather that by increasing cell proliferation, resulting in a larger CD8 + T cell memory pool [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2E). It is worth noting that IL-12 is known also to serve as a ''third signal'' for activated T cells [38,41,42]. In conclusion, we suggest a model in which MVA infection induces IFN that concomitantly acts directly on T cells and on DC to promote T-cell expansion, whereas VACV infection induces IL-12 that may compensate for leaking IFN and thus promotes IFNAR-independent T-cell expansion.…”
Section: Discussionmentioning
confidence: 73%
“…These effects of tumour cell fusion on DC phenotype and cytokine production may influence their interaction with naive T cells, 10 potentially facilitating priming by DC of an antitumour cytotoxic T-cell response. Therefore, the ability of fusing vs nonfusing tumour cell-loaded DC to prime a human naive T-cell response against Mel888 was determined.…”
Section: Priming Of Tumour-specific Ctl By DC Loaded With Intact or Fmentioning
confidence: 99%